Better together: Harnessing social relationships in smart energy communities. (August 2021) - Savelli, Iacopo; Morstyn, Thomas
Abstract: Social relationships can influence individual behaviours and personal choices, foster cooperation, and build solidarity. In this Perspective, we argue that harnessing social relationships connecting people living in the same community can help improve the functioning of smart local energy systems and facilitate cooperation towards shared objectives . These shared objectives could include reducing energy poverty, investing in clean technologies, and fostering energy justice. Therefore, we propose the new concept of smart energy neighbourhoods, which we define as a local energy system sharing (i) the same local energy infrastructure, (ii) a network of social relationships and group-focused concerns, and (iii) smart adaptive mechanisms enabling participation, coordination and cooperation. The paper discusses the beneficial role that smart energy neighbourhoods could play within future energy systems, their possible design, and key challenges for their implementation.